A new bound for t−wise almost universal hash functions - Nguyen, L; Roscoe, A (OUCL, 2010)
Using the pigeon-hole principle, we derive a new bound for the key length in a t-wise almost universal hash function where the multicollision or t-collision probability is bounded above by epsilon in the range [0,1]. The important features of this bound are (1) it decreases very slowly as t increases, and (2) the key length grows at least linearly with the logarithm of the message length. To our knowledge, this is the first almost universal hash bound for any integer t > 1. This work arises from the use of t-wise almost universal hash functions in manual authentication protocols.